Rhetoric Of The Question, The Dialogue Of Poetic Vision, A Reading Of Samples From The Collection Of "Sukrat Al - Qamar " By Amal Al-Qasim - Khalil Shukri Hayas; Marwa Mohamad Najeeb (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The poetic question is a subject that is expanding in critical studies to the extent, which is formed a private critical space. The poetic question was able to excrete during the reading a remarkable aesthetic and rhetorical aesthetic. It doubled the interest of critics and creators together and created dialogues between text and its recipients. Here in this research, the Dialogic means is not in the concept of the Bakhtni that depends on the intersexuality, but in its communicative concept for searching to the effectiveness of the poet in creating interactive dialogue between him and the implicit reader within the text and his default reader out of the text. This question dialogic creates a poetics distinctive and takes the technical reasons for dialogue from the technical side and even qualitative, and the question with elegance’s poetic. With this vision’s reading we have tried to analyze two patterns from poems of poet Amal AL-Qasim called (Cuffed eloquence) and (Sura water) which are standing on the poetic question to search inside both of the patterns on Aesthetic toward poetic and his ability to deepen the significance of the text and find out the poetic’s idealism and poetics.